Numerical Simulation and Experimental Validation of Melt Flow in the Naturally Pressurized Gating System - Marek Brůna (MDPI AG, 2021)
The main problem during the production of castings from aluminium alloys is the presence of the reoxidation, which negatively affects the final casting quality. Liquid metal surface reacts with the surrounding atmosphere and oxide layer of Al2O3 is formed on its surface. The problem occurs when the oxide layer is entrained to the internal volume of the melt by turbulence and double oxide layers are formed, also known as “bifilms”. Its formation is related to the melt velocity and gating system design. In paper, naturally pressurized gating system was calculated and designed. Effect of the filter media and vortex element on the melt velocity, amount of oxides, mechanical properties, and porosity were observed. Designs with 10 ppi and 20 ppi foam filters and vortex element were compared with design without filters to prove the positive (or negative) effect of filter media on melt velocity and thus on final casting quality. The melt velocity and amount of oxides were observed with the aid of simulation software. Mechanical properties, quantity of pores, bifilm index and EDX analysis were evaluated after experimental casts. It was proven that by using 20 ppi foam filter in combination with vortex element, the best results were achieved.